Low and high postpubertal ethanol use: damage on adulthood reproduction and offspring - Fioravante, Vanessa Caroline [UNESP]; Godoi, Alana Rezende [UNESP]; de Barros Camargo, Victória Mokarzel [UNESP]; Pinheiro, Patricia Fernanda Felipe [UNESP]; Martinez, Marcelo; Padovani, Carlos Roberto [UNESP]; Martinez, Francisco Eduardo [UNESP] (Bioscientifica, 2022)
The relationship between adolescent ethanol uses and its impacts throughout life are not conclusive. Thus, we evaluated if the low and high consumption of ethanol at postpuberty interferes with the reproduction and ethanol-naive offspring and if the effects are dose-related. Female and male rats were divided into three groups: low drinker (L), high drinker (H) and control (C). The L and H groups were exposed to ethanol up to 10 % from 65 to 80 days with withdrawal after this period. The ethanol consumed by low drinkers was 1.41 ± 0.21 g/kg/day and by high drinkers 4.59 ± 0.45 g/kg/day. The study was conducted in two phases. The first phase verified the reproductive capacity in adulthood on generations (litter size and sex ratio). Data were collected over 10 years. The second phase analyzed the parent reproductive parameters (body weight, reproductive organ weight, sperm parameters and estrous cycle) and the pup development. We observed a reduced litter size in both drinker groups. Gestational body weight gain and feed consumption were lower in L and H. We observed an alteration in reproductive organs weight in both sexes of H. Females presented a longer estrous cycle duration. Males presented an increase in abnormal sperm, a decrease in sperm count and accelerated transit time. The ethanol-naive offspring development was also impaired. We conclude that low and high postpubertal alcohol use impairs long-term reproductive parameters, even after alcohol withdrawal. There is also impaired ethanol-naive offspring. Besides, the effects are dose-related.
Keywords: alcohol; litter size; offspring; preconception; puberty; reproduction